Vanadoantimonates: from discrete clusters to high dimensional aggregates. Issue 27 (31st May 2016) - Guo, Hai-Yang; Zhang, Xiao; Cui, Xiao-Bing; Huo, Qi-Sheng; Xu, Ji-Qing
Abstract : Five new vanadoantimonates have been obtained under hydrothermal conditions and characterized. Abstract : Five new vanadoantimonates [Cd(en)3 ]3 [Sb6 V15 O42 (H2 O)]·8H2 O (1 ), [Ni(en)3 ]2 [H2 Sb6 V15 O42 (H2 O)]·5H2 O (2 ), [Co(en)3 ]2 [H2 Sb6 V15 O42 (H2 O)]·5H2 O (3 ), [H4 Sb8 V14 O42 (H2 O)]·5H2 O (4 ) and [Co(enMe)3 ]2 [Sb8 V14 O42 (H2 O)]·4H2 O (5 ) (en = ethylenediamine, enMe = 1, 2-propanediamine) have been obtained under hydrothermal conditions and characterized by IR, UV-Vis, XRD, ESR and CD spectroscopy. Compound1 is a chiral compound constructed from [Sb6 V15 O42 (H2 O)] 6− (Sb6 V15 ) and [Cd(en)3 ] 2+ . Compounds2 and3 are isostructural and isomorphous. Both compounds are chiral, each of which contains a 2-D inorganic layer formed by [H2 Sb6 V15 O42 (H2 O)] 4− via V–O⋯Sb contacts. Compound4 contains a 2-D inorganic layer formed by [H4 Sb8 V14 O42 (H2 O)], of which [H4 Sb8 V14 O42 (H2 O)] is directed by both V–O⋯Sb and Sb–O⋯Sb interactions. Compound5 contains a 1-D zigzag chain structure formed by [Sb8 V14 O42 (H2 O)] 4− (Sb8 V14 ) via Sb–O⋯Sb contacts.